2021
DOI: 10.3389/fonc.2020.627572
|View full text |Cite|
|
Sign up to set email alerts
|

Simultaneous Integrated Boost Intensity-Modulated Radiation Therapy Can Benefit the Locally Advanced Rectal Cancer Patients With Clinically Positive Lateral Pelvic Lymph Node

Abstract: Background and PurposeThe optimal treatment modality for clinically positive lateral pelvic lymph node (LPLN) from locally advanced rectal cancer (LARC) is unknown. Thus, we aimed to analyze the optimal radiotherapy dose for clinically positive LPLN from LARC.Materials and MethodsWe retrospectively evaluated distal LARC (i.e., within 8 cm from the anal verge) patients with clinically positive LPLN (i.e., ≥7 mm in the short axis). They were divided into two groups based on whether or not they received simultane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…Therefore, it allows smaller margins compared to non-adaptive strategies. Furthermore, we expect that the use of smaller margins in an online adaptive MRgRT setting allows for treatment intensification by increasing boost dosage on the tumor without additional OAR toxicity [32]. A change in margin size from 17 mm to 4 mm results in a substantial decrease in radiotherapy field size and irradiated healthy tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it allows smaller margins compared to non-adaptive strategies. Furthermore, we expect that the use of smaller margins in an online adaptive MRgRT setting allows for treatment intensification by increasing boost dosage on the tumor without additional OAR toxicity [32]. A change in margin size from 17 mm to 4 mm results in a substantial decrease in radiotherapy field size and irradiated healthy tissue.…”
Section: Discussionmentioning
confidence: 99%
“…However, our SIB approach is a novel strategy to address LPLN and stands as the first report of using a boost dose in the context of SCRT. 21 In addition, the definition of enlarged or suspicious LPLN remains somewhat variable and subject to interpretation bias across different radiologists. LLND was not performed to confirm positive LPLN status.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that more efficient treatment options need to be explored in the future to increase the LR rate for patients with LLN enlarged. Some studies suggested that boosting the radiotherapy dose for the involved LLN arrangement from 56 to 60.2 Gy can significantly lower the SA and effectively control the LR rate for rectal cancer, while radiotherapy‐related toxicity was acceptable 31–33 . This implies that boosting the radiotherapy dose to the presumed positive lateral lymph nodes may be an effective therapy.…”
Section: Discussionmentioning
confidence: 99%